Biografi Intelektual Pendiri UIN Raden Fatah Palembang dan Warisan Pemikiran Pendidikan Islam - Otoman Otoman; Muhammad Adil; Rr. Rina Antasari; Padila Padila; Romli Romli; Dur Brutu; Furi Azhira; Muhammad Alif Athillah; Ardian Mustaqim (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2025)
This study examines the intellectual biographies of the founders of the Raden Fatah State Islamic University (UIN) Palembang and their intellectual legacy in the development of Islamic education in Indonesia. This research uses a qualitative approach with historical methods, encompassing heuristics, verification, interpretation, and historiography. The results indicate that the founders of UIN Raden Fatah envisioned a moderate, integrative, and scientifically advanced vision of Islamic education. Their thinking became the foundation for the institutional transformation of IAIN into UIN and strengthened the integrative-interconnected scientific paradigm within the university. This intellectual legacy has not only been influential locally but has also contributed to the development of Islamic education discourse in Indonesia in general.